Teacher Experience to Employ Technological Pedagogical Knowledge in Teaching English: An Autobiographical Narrative - Rahmadilla Kurniasari; Diah Kristina; Sumardi Sumardi (STAI Hubbulwathan Duri, 2024)
Previous studies have discussed TPACK's constructions in the last decade, which focus on teacher professional development, survey TPACK’s (Technology, Pedagogy, and Content Knowledge) enactment, experimental, and teacher TPACK’s profile. A few studies are focused on the subdomains of TPACK, TPK (Technological Pedagogical Knowledge), which discusses how teachers' experiences practice TPK. It has become a new scope of exploration in Indonesia. The present study aims to narrate my meaningful story by employing technological and pedagogical in teaching English to Vocational High Schools. It will focus on how I practice TPK as a novice teacher in Indonesia's private Vocational High School. The data was collected through my teaching diary and supported with students' artifacts. This research is grounded in an autobiographical narrative, which explores the meaningful story of the narrator. The finding of this study reveals that the researcher, as a novice teacher, can employ TPK in teaching English by joining professional teacher development and self-awareness to make innovations in using technology and provide different learning activities using technologies. The present study might bring future research contributions for preparing TPK, reflecting TPK, and evaluating TPK in teaching English for Foreign Language (EFL).